Difficult decisions : how leaders make the right call with insight, integrity, and empathy - Pliner, Eric (John Wiley & Sons, Inc., 2022)
"For every algorithm that purports to mitigate bias, enable sophisticated thinking under time pressure, or leverage big data to simplify complex questions, there are loads of choices that require creative, reflective, and thoughtful interpretation of subjective human experience -- something artificial intelligence and rigorous analytics cannot yet replicate. What do we do when the obvious conclusion from a rigorous spreadsheet doesn't align to our core beliefs about leadership, organizations, business, communities, or people? This book sets aside the conventional wisdom of decision-making in favor of a set of practical tools for understanding our own subjectivity and how it does -- and should -- influence how we make the most difficult choices. Readers/leaders will build sharp self-reflection, clarification of values, deep understanding of their own morality in a shifting ethical context, and how to navigate conflict among these. Whether in business, education, politics, the arts, or any other kind of leadership, when the job that we think we're here to do seems to challenge the values that sit at the heart of leadership, we need a way to make sense of it all -- quickly, meaningfully, and with integrity."--